Brain anatomy differences in Chinese children who stutter: a preliminary study - Ma, Dan; Wang, Lingling; Liu, Sai; Ma, XinMao; Jia, Fenglin; Hua, Yimin; Liao, Yi; Qu, Haibo (Frontiers in Neurology, 2025)
Background and purposeIt is unknown the neural mechanisms of developmental stuttering (DS). The aim of this study was to investigate the changes in the structural morphology of the brain in Chinese children who stutter.MethodsA case–control study was conducted to collect magnetic resonance imaging data from stuttering and non-stuttering children, thereby analyzing whole-brain gray matter volume and cortical morphological changes in stuttering children.ResultsA total of 108 subjects were recruited (stuttering group: control group = 1:1). Comparing to healthy controls, the gray matter volume was significantly decreased in right temporal gyrus and bilateral cerebellum. Additionally, there was a significant reduction in cortical folds in the right insula and right superior temporal gyrus. Moreover, the gray matter volume of the right cerebellum and right temporal gyrus is related to the severity score of stuttering.ConclusionThe present study proposes that the neural mechanisms underlying DS are intricately linked to the cortico-basal ganglia-thalamo-cortical loop and the dorsal language pathway. This finding is expected to provide reference value for the clinical treatment of DS.